Bounds on coefficients for a class of Analytic functions Defined by Quasi-Subordination - Jalawi Abd, Sarah; Fouad Abduljabbar, Meena (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
This study delineates particular subclasses of analytic univalent functions linked to quasi-subordination and establishes results including coefficient bounds and Fekete-Szego problem for functions inside these subclasses.